Mobile Learning Game Effectiveness in Cognitive Learning by Adults: A Comparative Study. (August 2017) - Wardaszko, Marcin; Podgórski, Błażej
Background . The effectiveness ofdigital game-based learning is an important issue.Mobile learning games (MLG) are rapidly growing trends among the digital game-based learning genre. Although many studies have been conducted and mobile games have been shown to have an unquestionable potential as a learning method, their effectiveness has not been fully proven, and the positive impacts and outcomes of mobile learning games with respect to learning have yet to be investigated. Aim. The study aimed at capturing thecognitive learning outcomes and the process of knowledge acquisition. The study has demonstrated both positive and negative cognitive learning effects of using mobile learning game in comparison with the textbook learning process. Methodology. This article presents acomparative study conducted on a group of 160 freshman students majoring in management and finance. The participants of the study, divided into subgroups, were taught using eithertextbook-based learning or amobile learning game . Threetests were applied to measure their performance: apre-test at the beginning of the experiment, andtwo post-tests, the first administered directly after the learning process and the second 2-3 weeks after the initial learning. Results and recommendations. MLG have been proven to create manypositive effect for learning . It is as effective in transferring factual knowledge as textbook learning, when measured directly after the learning process. In longer term, the effects are blurred because the affective effects interfere with the measurement.